University student's digital reading and writing migration (2012)
This paper discusses the impact of new electronic media on young university student's reading and writing habits. The methodological design is ethnographic and involved an observation register of reading and writing situations. The analysis was based on several categories: written-material culture, text-screen interaction, intertextuality, digital migration and the convergence of literacies. The results show that the digital migration of university readers and writers is evident from the way they structure a document, from Google's influence on the search for and selection of documentary and bibliographic sources, and from the way they incorporate citations in texts.